Influence of the Internet on the Cognitive Abilities of Man. Phenomenological and Hermeneutical Approach - Slavomír Gálik; Sabína Gáliková Tolnaiová (Communication Today, 2025)
In this article, the authors study the influence of the Internet on human cognitive abilities using a phenomenological and hermeneutical approach. They characterize the Internet as an electronic or technological form of media communication facilitating nearly instantaneous and active dissemination of information, in particular image-based information. The authors study the Internet’s influence on the cognitive abilities of humans using a definition of the Internet as multilaterally connected information networks. Applying the theoretical approach, they reach the conclusion that newly formulated thinking strategies feature a network-like character to the detriment of the ability to observe, remember and other higher levels of thinking. The empirical approach is based on neurological and sociological studies which reveal the fact that new ways or strategies of thinking are being fixed in the brain, thereby driving long-term and permanent changes in human thinking. In such a case, the inability to concentrate on one idea for an extended period of time in order to reach a deeper state of contemplation proves to be at risk. In connection to this, we may encounter, as the authors believe, symptoms of knowledge deficiency resulting from a loss of interest in linear, chronological thinking. The authors claim that knowing these risks should lead to a more careful and more critical approach to the Internet, or even Internet communication, which may partially mitigate its negative influence.